PENGARUH MODEL CASE BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR INTUITIF MATEMATIS SISWA - Alfiyah, Khansa; Atiqoh, Khamida Siti Nur; Kurniawati, Lia (Faculty of Educational sciences, UIN Syarif Hidayatullah Jakarta, 2025)
Abstract The 2022 PISA results reveal that students' mathematical intuitive thinking remains low. To enhance this ability, learning must actively engage students in constructing understanding and stimulating their intuition. The purpose of this study was to determine whether or not there is an effect of the CBL model on students' mathematical intuitive thinking abilities. This study used a quantitative method with a quasi-experimental type with a posttest-only control group design. The population in this study were all eighth-grade students of a junior high school in South Tangerang. The sample size was 60 students, namely 30 students in the experimental group and 30 students in the control group with a purposive sampling technique. The instrument used in this study was a mathematical intuitive thinking ability test instrument. The results of this study showed that the sig. value = 0.000 is smaller than the 0.05 significance standard in the hypothesis test. This indicates that the average mathematical intuitive thinking ability of students in statistics material taught using the CBL model is higher than that of students taught using the Direct Instruction learning model. This study concludes that learning mathematics using the CBL model has an effect on students' mathematical intuitive thinking abilities. Abstrak Hasil PISA 2022 menunjukkan bahwa kemampuan berpikir intuitif matematis siswa masih rendah. Untuk meningkatkan kemampuan ini, proses pembelajaran perlu melibatkan siswa secara aktif dalam membangun pemahaman dan menumbuhkan intuisi matematis mereka. Tujuan dilakukan penelitian ini untuk menentukan ada tidaknya pengaruh model CBL terhadap kemampuan berpikir intuitif matematis siswa. Penelitian ini menggunakan metode kuantitatif dengan jenis quasi-eksperimen berdesain posttest only control group design. Populasi dalam penelitian ini yaitu seluruh siswa kelas VIII salah satu SMP di Tangerang Selatan. Sampel berjumlah 60 siswa, yaitu 30 siswa kelompok eksperimen dan 30 siswa kelompok kontrol dengan teknik purposive sampling. Instrumen yang digunakan dalam penelitian ini adalah instrumen tes kemampuan berpikir intuitif matematis. Hasil penelitian ini menunjukkan bahwa nilai sig. = 0,000 lebih kecil dari standar signifikansi 0,05 pada uji hipotesis. Hal ini menunjukkan bahwa rata-rata kemampuan berpikir intuitif matematis siswa pada materi statistika yang diajar menggunakan model CBL lebih tinggi daripada siswa yang diajar dengan model Direct Instruction. Penelitian ini menyimpulkan bahwa pembelajaran matematika menggunakan model CBL berpengaruh terhadap kemampuan berpikir intuitif matematis siswa.